Stabilization treatment method for iron-aluminum slag containing Ni, Co and F
By adjusting the pH value and adding calcium-containing substances and phosphate ion solutions, the divalent cobalt is oxidized by air and forming stable phosphate compounds, the stabilization problems of Ni, Co, and F in iron and aluminum slag are solved, and low-cost is achieved The deep stabilization treatment avoids the use of high temperature and high pressure conditions.
Patent Information
- Application Number
- CN202411326154.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to effectively stabilize the treatment of Ni, Co, F containing iron and aluminum slags within a cost-acceptable range, especially divalent cobalt oxidation difficulties and cobalt stabilization, and when calcium-based solids stabilize fluorine It is easy to generate a parcel to prevent cobalt from oxidation, resulting in high processing costs and difficult to promote.
By mixing iron and aluminum slag with water and adding alkaline substances, adjusting the pH value, and then adding calcium-containing substances and phosphate ion solutions, controlling the pH value within the range of 8-9, using air to achieve oxidation of divalent cobalt, and through The formation of trivalent cobalt and stable phosphate compounds achieves the stabilization of Ni and F, avoiding high temperature and high pressure conditions.
Effective oxidation of divalent cobalt at room temperature and pressure will reduce the leaching toxicity of cobalt, achieve deep stability of Ni, Co, and F, reduce processing costs, and improve the feasibility of treatment effects and industrial promotion.
Smart Images

Figure CN119237446A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste treatment, and in particular relates to a stabilization treatment method for iron-aluminum slag containing Ni, Co and F. Background Art
[0002] Ferroaluminum slag is the slag with the highest output in the battery recycling process. Due to its complex composition, high value-added utilization is difficult and the market consumption is limited, therefore, it is of great significance to explore the stabilization treatment method of environmentally harmful elements Ni, Co, and F in ferroaluminum slag to reduce the environmental pollution caused by ferroaluminum slag during storage. However, the main difficulties in achieving effective solidification of ferroaluminum slag within an acceptable cost range are as follows: (1) The solubility product constant of divalent cobalt salt is relatively large and highly soluble in the environment. Divalent cobalt needs to be converted into trivalent cobalt to achieve deep stabilization of cobalt. However, cobalt has a high oxidation potential and is difficult to oxidize divalent cobalt. Under normal conditions, it is difficult to achieve effective oxidation of cobalt by directly reacting hydrogen peroxide, oxygen, etc. with cobalt salts; (2) When calcium-based solids are used to stabilize fluorine, calcium fluoride or calcium sulfate is easily generated to encapsulate cobalt, preventing the contact between cobalt and the oxidant, making oxidation of cobalt difficult; (3) Stabilization cost. If a more expensive oxidant or more harsh (high temperature and high pressure) reaction conditions are used, it will be difficult to be accepted by the market and to achieve large-scale promotion. Therefore, there is an urgent need to provide a stabilization treatment method with good treatment effect and low treatment cost. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the present invention proposes a stabilization treatment method for iron-aluminum slag containing Ni, Co and F, which has good stabilization effect and low treatment cost.
[0004] The above technical objectives of the present invention are achieved through the following technical solutions:
[0005] A method for stabilizing ferroaluminum slag containing Ni, Co, and F comprises the following steps: (1) mixing the ferroaluminum slag with water to form a first slurry, adding an alkaline substance under the condition of continuous air flow, and reacting after stirring to obtain a second slurry; (2) adding a calcium-containing substance and a phosphate ion solution to the second slurry in sequence under the condition of continuous air flow and stirring, and adjusting the pH of the second slurry to ≥8, performing solid-liquid separation after the reaction, and obtaining a filtrate and the ferroaluminum slag after stabilization.
[0006] In one embodiment, in step (1), the iron-aluminum slag is the waste slag produced by removing iron and aluminum during the recovery process of the positive electrode material of the ternary battery, which includes the following composition elements in weight proportion: Fe: 16%-23%, Al: 7%-12%, S: 5%-13%, Na: 4%-8%, P: 1.2%-2%, F: 1%-3%, Ni: 0.3%-1.0%, Co: 0.2%-1.2%, Mn: 0.5%-1.4%. The rest is mainly O element and H element.
[0007] In one embodiment, in step (1), the mass ratio of the iron-aluminum slag to water is: 1:(2-4).
[0008] In one embodiment, in step (1), the alkaline substance is at least one of sodium carbonate, sodium hydroxide, sodium silicate, potassium carbonate, potassium hydroxide and potassium silicate.
[0009] In one embodiment, in step (1), an alkaline substance is added to adjust the pH of the first slurry to 6-7.
[0010] In one embodiment, in step (1), the reaction time is 30-60 min.
[0011] In one embodiment, in step (2), a calcium-containing substance and a phosphate ion-containing solution are added and the pH of the second slurry is adjusted to 8-9.
[0012] In one embodiment, in step (2), the calcium-containing substance is at least one of calcium hydroxide, calcium oxide, calcium sulfate, carbide slag and phosphogypsum.
[0013] In one embodiment, in step (2), the phosphate ion-containing solution is at least one of sodium phosphate, potassium phosphate, ammonium phosphate, phosphoric acid, calcium phosphate and phosphate ion-containing wastewater.
[0014] In one embodiment, in step (2), the ratio of the molar amount of calcium in the added calcium-containing substance to the molar amount of F element in the second slurry is (1-3):1, and the molar amount of phosphate ions in the added phosphate ion-containing solution is not greater than the sum of the molar amounts of Ni, Co, Mn, and F elements in the second slurry.
[0015] In one embodiment, in step (2), the reaction time is 2-3 hours.
[0016] In one embodiment, in step (2), the filtrate is returned to the second slurry for recycling.
[0017] The beneficial effects of the present invention are:
[0018] (1) The present invention reduces the oxidation potential of divalent cobalt by regulating the pH value of the iron-aluminum slag, and can effectively oxidize divalent cobalt by using air under normal temperature and pressure conditions, with low processing cost, thereby avoiding the problem that the solidification cost is too high due to the difficulty in oxidizing cobalt and the use of oxidants such as hydrogen peroxide and sodium persulfate, which is not conducive to large-scale industrial implementation;
[0019] (2) The present invention utilizes the principle that the solubility of Co(OH)3 and Co3(PO4)3 formed by trivalent cobalt is much lower than that of Co(OH)2 and CoHPO4, and converts divalent cobalt into trivalent cobalt to achieve effective stabilization of cobalt, thereby greatly reducing the leaching toxicity of cobalt;
[0020] (3) The present invention adopts a two-step alkali adjustment method, that is, firstly, the pH of the solution is adjusted to 6-7 by using a highly soluble alkali such as NaOH or Na2CO3, thereby reducing the oxidation potential of Co(II) and oxidizing Co(II) to Co(III) by air; then, calcium-containing substances are used to solidify soluble F into highly stable CaF2; at the same time, by controlling the pH of the solution at 8-9 and adding substances containing phosphate ions, soluble nickel is converted into Ni(OH)2 and Ni3(PO4)2 to achieve Ni stabilization;
[0021] (4) In the present invention, during the reaction process, air is continuously introduced, which can not only promote the effective oxidation of Co and avoid the conversion of oxidized Co(III) into Co(II) again, but also greatly promote solid-liquid contact, avoid the problem of insufficient reaction caused by rapid precipitation due to excessive local alkali concentration, avoid the formation of film-like precipitates on the surface of the particles during the reaction, prevent the problem of incomplete reaction of elements inside the particles, and improve the uniformity of the solution and the stabilization effect of Ni, Co, and F. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the process of Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with specific embodiments.
[0024] Embodiment 1:
[0025] A stabilization treatment method for iron-aluminum slag containing Ni, Co and F, such as Figure 1 As shown, the following steps are included:
[0026] (1) 100 g of iron-aluminum slag and 250 g of aqueous solution were mixed to prepare a first slurry. Under the condition of continuous air flow, NaOH was added to adjust the pH of the first slurry to 6, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0027] (2) Under the condition of continuous air flow and stirring, 20.55 g of carbide slag (calcium hydroxide content is 90%) and 50 mL of sodium phosphate solution (phosphate ion concentration is 2 mol / L) are added to the second slurry, the pH of the second slurry is adjusted to 9, and stirred for 3 h. After the reaction, solid-liquid separation is performed to obtain a filtrate and stabilized iron-aluminum slag, and the filtrate is recycled to the second slurry. The constituent elements and weight proportions included in the iron-aluminum slag used in this embodiment are: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O elements and H elements. According to the national standard method HJ / T 299-2007, Ni, Co, and Mn are detected using an ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co, and F in the iron-aluminum slag is reduced from 335 mg / L, 91 mg / L, and 167 mg / L to 0.1 mg / L, 0.1 mg / L, and 9.3 mg / L, respectively (the national standard requirements are 5 mg / L, 5 mg / L, and 100 mg / L, respectively), indicating that Ni, Co, and F are effectively solidified.
[0028] Embodiment 2:
[0029] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0030] (1) 100 g of iron-aluminum slag was mixed with 300 g of aqueous solution to prepare a first slurry, and Na2CO3 was added to adjust the pH of the first slurry to 7 under the condition of continuous air flow, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0031] (2) Under the condition of continuous air supply and stirring, 40 g of phosphogypsum (calcium hydroxide content of 37%, calcium sulfate content of 51%) and 50 mL of sodium phosphate solution (phosphate ion concentration of 2 mol / L) were added to the second slurry, and the pH of the second slurry was adjusted to 9. The mixture was stirred for 3 h. After the reaction, solid-liquid separation was performed to obtain a filtrate and stabilized iron-aluminum slag. The filtrate was recycled into the second slurry. The constituent elements and weight proportions included in the iron-aluminum slag used in this embodiment are: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O elements and H elements. According to the national standard method HJ / T 299-2007, Ni, Co, and Mn are detected using an ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co, and F in the iron-aluminum slag is reduced from 335 mg / L, 91 mg / L, and 167 mg / L to 0.1 mg / L, 0.1 mg / L, and 9.3 mg / L, respectively (the national standard requirements are 5 mg / L, 5 mg / L, and 100 mg / L, respectively), indicating that Ni, Co, and F are effectively solidified.
[0032] Example 3: (The only difference from Example 1 is that the pH is adjusted to 8 in step (1))
[0033] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0034] (1) 100 g of iron-aluminum slag and 250 g of aqueous solution were mixed to prepare a first slurry. Under the condition of continuous air flow, NaOH was added to adjust the pH of the first slurry to 8, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0035] (2) Under the condition of continuous air flow and stirring, 20.55 g of carbide slag (calcium hydroxide content of 90%) and 50 mL of sodium phosphate solution (phosphate ion concentration of 2 mol / L) were added to the second slurry, and the pH of the second slurry was adjusted to 9. The mixture was stirred for 3 h. After the reaction, solid-liquid separation was performed to obtain a filtrate and stabilized iron-aluminum slag. The filtrate was recycled into the second slurry. The constituent elements and weight proportions included in the iron-aluminum slag used in this embodiment are: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O elements and H elements. According to the national standard method HJ / T 299-2007, Ni, Co, and Mn are detected using an ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co, and F in the iron-aluminum slag is reduced from 335 mg / L, 91 mg / L, and 167 mg / L to 0.1 mg / L, 0.1 mg / L, and 9.3 mg / L, respectively (the national standard requirements are 5 mg / L, 5 mg / L, and 100 mg / L, respectively), indicating that the first step is to adjust the pH to be greater than 7, and the second step is to adjust the pH to 9, which has no effect on the effective solidification of Ni, Co, and F. Considering that most calcium-containing reagents are alkaline, the preferred pH in the first step is 6-7.
[0036] Example 4: (The only difference from Example 1 is that the pH is adjusted to 10 in step (2))
[0037] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0038] (1) 100 g of iron-aluminum slag and 250 g of aqueous solution were mixed to prepare a first slurry. Under the condition of continuous air flow, NaOH was added to adjust the pH of the first slurry to 6, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0039] (2) Under the condition of continuous air flow and stirring, 20.55 g of carbide slag (calcium hydroxide content of 90%) and 50 mL of sodium phosphate solution (phosphate ion concentration of 2 mol / L) were added to the second slurry, the pH of the second slurry was adjusted to 10, and the mixture was stirred for 3 h. After the reaction, solid-liquid separation was performed to obtain a filtrate and stabilized iron-aluminum slag, and the filtrate was recycled into the second slurry. The iron-aluminum slag used in this embodiment includes the following elements and their weight ratios: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O and H elements. According to the national standard method HJ / T 299-2007, Ni, Co, and Mn are detected using an ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co, and F in the iron-aluminum slag is reduced from 335 mg / L, 91 mg / L, and 167 mg / L to 0.1 mg / L, 0.1 mg / L, and 68 mg / L, respectively (the national standard requirements are 5 mg / L, 5 mg / L, and 100 mg / L, respectively), which meets the national standard requirements. However, the pH adjusted in step (2) is relatively high, which will lead to a poor stabilization effect of F.
[0040] Comparative Example 1: (The only difference from Example 1 is that no air is passed during the treatment process)
[0041] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0042] (1) 100 g of iron-aluminum slag was mixed with 250 g of aqueous solution to prepare a first slurry, NaOH was added to adjust the pH of the first slurry to 6, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0043] (2) Under continuous stirring, 20.55 g of carbide slag (calcium hydroxide content is 90%) and 50 mL of sodium phosphate solution (phosphate ion concentration is 2 mol / L) are added to the second slurry, the pH of the second slurry is adjusted to 9, and the mixture is stirred for 3 h. After the reaction, solid-liquid separation is performed to obtain a filtrate and stabilized iron-aluminum slag, and the filtrate is recycled into the second slurry. The constituent elements and weight proportions of the ferroaluminum slag used in this comparative example are: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O elements and H elements. According to the national standard method HJ / T 299-2007, Ni, Co and Mn are detected by ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co and F in the ferroaluminum slag is reduced from 335mg / L, 91mg / L and 167mg / L to 0.9mg / L, 20mg / L and 32mg / L respectively (the national standard requirements are 5mg / L, 5mg / L and 100mg / L respectively), indicating that the leaching toxicity of cobalt is difficult to meet the standard without air in the treatment process.
[0044] Comparative Example 2: (The only difference from Example 1 is that air is not continuously introduced)
[0045] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0046] (1) 100 g of iron-aluminum slag and 250 g of aqueous solution were mixed to prepare a first slurry, and air was introduced to react for 10 h, then the introduction of air was stopped, and NaOH was added to adjust the pH of the first slurry to 6, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0047] (2) Under continuous stirring, 20.55 g of carbide slag (calcium hydroxide content of 90%) and 50 mL of sodium phosphate solution (phosphate ion concentration of 2 mol / L) were added to the second slurry, and the pH of the second slurry was adjusted to 9. The mixture was stirred for 3 h. After the reaction, solid-liquid separation was performed to obtain a filtrate and stabilized iron-aluminum slag. The filtrate was recycled into the second slurry. The constituent elements and weight proportions of the ferroaluminum slag used in this comparative example are as follows: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O and H elements. According to the national standard method HJT 299-2007, Ni, Co, and Mn are detected by ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co, and F in the ferroaluminum slag is reduced from 335 mg / L, 91 mg / L, and 167 mg / L to 1 mg / L, 45 mg / L, and 38 mg / L, respectively (the national standard requirements are 5 mg / L, 5 mg / L, and 100 mg / L, respectively), indicating that before the pH of the ferroaluminum slag is not adjusted, the air cannot oxidize Co(II) to Co(III). Only by oxidizing Co(II) to Co(III) 2+ Deep stabilization of Co cannot be achieved by conversion to Co(OH)2 or Co3(PO4)2.
[0048] Comparative Example 3: (The only difference from Example 1 is that no calcium-containing substance is added in step (2))
[0049] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0050] (1) 100 g of iron-aluminum slag and 250 g of aqueous solution were mixed to prepare a first slurry. Under the condition of continuous air flow, NaOH was added to adjust the pH of the first slurry to 6, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0051] (2) Under the condition of continuous air flow and stirring, 50 mL of sodium phosphate solution (phosphate ion concentration is 2 mol / L) is added to the second slurry, and NaOH is added to adjust the pH of the second slurry to 9. The mixture is stirred for 3 h. After the reaction, solid-liquid separation is performed to obtain a filtrate and stabilized iron-aluminum slag. The filtrate is recycled into the second slurry. The constituent elements and weight proportions of the ferroaluminum slag used in this comparative example are: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O elements and H elements. According to the national standard method HJ / T 299-2007, Ni, Co and Mn are detected by ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co and F in the ferroaluminum slag is reduced from 335mg / L, 91mg / L and 167mg / L to 0.1mg / L, 0.1mg / L and 130mg / L respectively (the national standard requirements are 5mg / L, 5mg / L and 100mg / L respectively), indicating that effective solidification of F cannot be achieved without adding calcium-containing substances.
[0052] Comparative Example 4: (The only difference from Example 1 is that after adjusting the pH in step (1), step (2) is directly performed without stirring and mixing for 30 minutes)
[0053] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0054] (1) 100 g of iron-aluminum slag and 250 g of aqueous solution were mixed to prepare a first slurry, and NaOH was added to adjust the pH of the first slurry to 6 under the condition of continuous air flow to obtain a second slurry;
[0055] (2) Under the condition of continuous air flow, 20.55 g of carbide slag (calcium hydroxide content of 90%) and 50 mL of sodium phosphate solution (phosphate ion concentration of 2 mol / L) were added to the second slurry, and the pH of the second slurry was adjusted to 9. The mixture was stirred for 3 h. After the reaction, solid-liquid separation was performed to obtain a filtrate and stabilized iron-aluminum slag. The filtrate was recycled into the second slurry. The constituent elements and weight proportions of the ferroaluminum slag used in this comparative example are: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O elements and H elements. According to the national standard method HJ / T 299-2007, Ni, Co, and Mn are detected by ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co, and F in the ferroaluminum slag is reduced from 335 mg / L, 91 mg / L, and 167 mg / L to 0.1 mg / L, 6.8 mg / L, and 10.1 mg / L, respectively (the national standard requirements are 5 mg / L, 5 mg / L, and 100 mg / L, respectively), indicating that the oxidation of Co is not thorough and the stabilization effect of Co does not meet the requirements.
[0056] Comparative Example 5: (The only difference from Example 1 is that the pH is adjusted to 7 in step (2))
[0057] A method for stabilizing ferroaluminum slag containing Ni, Co and F comprises the following steps:
[0058] (1) 100 g of iron-aluminum slag and 250 g of aqueous solution were mixed to prepare a first slurry. Under the condition of continuous air flow, NaOH was added to adjust the pH of the first slurry to 6, and the mixture was stirred and reacted for 30 min to obtain a second slurry;
[0059] (2) Under the condition of continuous air flow and stirring, 20.55 g of carbide slag (calcium hydroxide content of 90%) and 50 mL of sodium phosphate solution (phosphate ion concentration of 2 mol / L) were added to the second slurry, and the pH of the second slurry was adjusted to 7. The mixture was stirred for 3 h. After the reaction, solid-liquid separation was performed to obtain a filtrate and stabilized iron-aluminum slag. The filtrate was recycled into the second slurry. The iron-aluminum slag used in this comparative example includes the following elements and their weight proportions: Fe: 18%, Al: 8%, S: 10%, Na: 6%, P: 1.5%, F: 2.5%, Ni: 1.0%, Co: 0.8%, Mn: 0.5%, and the rest are mainly O and H elements. According to the national standard method HJ / T 299-2007, Ni, Co and Mn are detected by ICP detector. After stabilization treatment, the leaching toxicity of Ni, Co and F in the iron-aluminum slag is reduced from 335 mg / L, 91 mg / L and 167 mg / L to 10.5 mg / L, 5.8 mg / L and 31 mg / L respectively (the national standard requirements are 5 mg / L, 5 mg / L and 100 mg / L respectively). This indicates that when the pH value is adjusted to a value <8 in step (2), the stabilization effect of Ni, Co and F will be reduced, and the leaching toxicity of Ni and Co cannot meet the national standard requirements.
Claims
1. A method for stabilizing ferroaluminum slag containing Ni, Co and F, characterized in that: The following steps are involved: (1) mixing iron-aluminum slag with water to prepare a first slurry, adding an alkaline substance while continuously introducing air, and reacting after stirring to obtain a second slurry; (2) Under the condition of continuous air supply and stirring, adding a calcium-containing substance and a phosphate ion solution to the second slurry and adjusting the pH of the second slurry to ≥ 8, performing solid-liquid separation after the reaction, and obtaining a filtrate and a stabilized iron-aluminum slag.
2. The method for stabilizing ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (1), the iron-aluminum slag is the waste slag produced by removing iron and aluminum during the recovery process of the positive electrode material of the ternary battery, which includes the following component elements in weight proportion: Fe: 16%-23%, Al: 7%-12%, S: 5%-13%, Na: 4%-8%, P: 1.2%-2%, F: 1%-3%, Ni: 0.3%-1.0%, Co: 0.2%-1.2%, Mn: 0.5%-1.4%.
3. The method for stabilizing the ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (1), the alkaline substance is at least one of sodium carbonate, sodium hydroxide, sodium silicate, potassium carbonate, potassium hydroxide and potassium silicate.
4. The method for stabilizing the ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (1), an alkaline substance is added to adjust the pH of the first slurry to 6-7.
5. The method for stabilizing ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (1), the reaction time is 30-60 min.
6. The method for stabilizing ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (2), a calcium-containing substance and a phosphate ion solution are added and the pH of the second slurry is adjusted to 8-9.
7. The method for stabilizing ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (2), the calcium-containing substance is at least one of calcium hydroxide, calcium oxide, calcium sulfate, carbide slag and phosphogypsum.
8. The method for stabilizing ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (2), the phosphate ion-containing solution is at least one of sodium phosphate, potassium phosphate, ammonium phosphate, phosphoric acid, calcium phosphate and phosphate ion-containing wastewater.
9. The method for stabilizing ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (2), the reaction time is 2-3 hours.
10. The method for stabilizing ferroaluminum slag containing Ni, Co and F according to claim 1, characterized in that: In step (2), the filtrate is returned to the second slurry for recycling.
Citation Information
Patent Citations
Method for preparing lithium-rich solid solution anode material by gas oxidation-coprecipitation method
CN102867952A
Comprehensive utilization method for iron-aluminum slag
CN105506290A
Preparation method for porous carrier-loaded nano-cobalt catalyst
CN106582651A
Method for recycling nickel, cobalt, iron and aluminum slag resources
CN115896462A
Method for resource utilization of iron-aluminum slag
CN116103502A
Cited By
Comprehensive recovery method for ferroalumen slag
CN120666192A
